Political dynamics promoting the incremental regulation of secondhand smoke: a case study of New South Wales, Australia - Chapman Simon; Bryan-Jones Katherine (BMC, 2006)
Abstract Background The history of governmental responses to the accumulation of scientific evidence about the harms of secondhand smoke (SHS) presents an intriguing case study of incremental public health policy development. Australia has long been considered a world-leader in progressive tobacco control policies, but in the last decade has fallen behind other jurisdictions in introducing SHS legislation that protects all workers. Bars, clubs and pubs remain the only public indoor spaces where smoking is legally permitted, despite SHS exposure in the hospitality industry being higher and affecting more people than in any other setting after domestic exposure. This paper examines the political dynamics that have shaped this incremental approach to SHS. Methods In-depth interviews with 21 key stakeholders in the state of New South Wales (NSW), including politicians, their advisors, health officials and tobacco control advocates, were conducted and subjected to thematic content analysis. Interviewees' comments provided insights into the dynamics surrounding the debates and outcomes of SHS legislative attempts and the current political environment, and about how to progress SHS legislation. Results SHS restrictions have been delayed by several broad factors: the influence of industry groups successfully opposing regulation; issue wear-out; and political perceptions that there is not a salient constituency demanding that smoking be banned in bars and clubs. Interviewees also provided suggestions of strategies that advocates might utilise to best overcome the current political inertia of incremental compromises and achieve timely comprehensive smoking bans. Conclusion Advocates concerned to shorten the duration of incremental endgames must continue to insist that governments address SHS fundamentally as a health issue rather than making political concessions to industry groups, and should broaden and amplify community voices calling on governments to finish the job. Publicity to the growing number of state and national governments that have successfully implemented total bans over the past decade is likely to make incrementalism an increasingly unattractive political option.